2010
DOI: 10.3189/002214310792447725
|View full text |Cite
|
Sign up to set email alerts
|

Effects of debris on ice-surface melting rates: an experimental study

Abstract: ABSTRACT. Here we report a laboratory study of the effects of debris thickness, diurnally cyclic radiation and rainfall on melt rates beneath rock-avalanche debris and sand (representing typical highly permeable supraglacial debris). Under continuous, steady-state radiation, sand cover >50 mm thick delays the onset of ice-surface melting by >12 hours, but subsequent melting matches melt rates of a bare ice surface. Only when diurnal cycles of radiation are imposed does the debris reduce the longterm rate of ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
144
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(152 citation statements)
references
References 26 publications
(45 reference statements)
8
144
0
Order By: Relevance
“…The presence of supraglacial debris allows for glacier tongues to extend to much lower-lying elevations than would otherwise be possible (Owen and Benn, 2005). The effects of debris-cover on glacier mass balance are poorly known, and can act to either retard or exacerbate glacier melting depending on debris thickness, composition, and distribution (Reznichenko et al, 2010;Zhang et al, 2011). Many studies have reported thresholds of debris-thickness, above which the debris acts to insulate the glacier as opposed to amplifying melt rates (Reznichenko et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of supraglacial debris allows for glacier tongues to extend to much lower-lying elevations than would otherwise be possible (Owen and Benn, 2005). The effects of debris-cover on glacier mass balance are poorly known, and can act to either retard or exacerbate glacier melting depending on debris thickness, composition, and distribution (Reznichenko et al, 2010;Zhang et al, 2011). Many studies have reported thresholds of debris-thickness, above which the debris acts to insulate the glacier as opposed to amplifying melt rates (Reznichenko et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The porosity and thickness of the surface debris enables a saturated debris layer to develop (Reznichenko et al, 2010;Collier et al, 2014). Rapid downslope transport of surface water occurs in areas of steep relief, but the surface debris may lead to the formation of shallow groundwater lenses in lowslope areas.…”
Section: Introductionmentioning
confidence: 99%
“…Reznichenko et al [124] studied the effects of debris-cover on glacier ice in a laboratory environment. The insulating effect of thicker debris-cover (greater than 5 cm) is only possible when diurnal cycles of radiation forcing are present, as nighttime allows for the absorbed energy to be emitted back to the atmosphere.…”
Section: Debris-covermentioning
confidence: 99%